Effects and metabolism of fish collagen sponge in repairing acute wounds of rat skin - Wang, Lei; Qu, Yan; Li, Wenjun; Wang, Kai; Qin, Song (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Study the repair effect of tilapia collagen on acute wounds, and the effect on the expression level of related genes and its metabolic direction in the repair process. Materials and Methods: After the full-thickness skin defect model was constructed in SD rats, the wound healing effect was observed and evaluated by means of characterization, histology, and immunohistochemistry. RT-PCR, fluorescence tracer, frozen section and other techniques were used to observe the effect of fish collagen on the expression of related genes and its metabolic direction in the process of wound repair. Results: After implantation, there was no immune rejection reaction, fish collagen fused with new collagen fibers in the early stage of wound repair, and was gradually degraded and replaced by new collagen in the later stage. It has excellent performance in inducing vascular growth, promoting collagen deposition and maturation, and re-epithelialization. The results of fluorescent tracer showed that fish collagen was decomposed, and the decomposition products were involved in the wound repair process and remained at the wound site as a part of the new tissue. RT-PCR results showed that, without affecting collagen deposition, the expression level of collagen-related genes was down-regulated due to the implantation of fish collagen. Conclusion: Fish collagen has good biocompatibility and wound repair ability. It is decomposed and utilized in the process of wound repair to form new tissues.